Package design for frozen foods: principles for sustainability - Delfino, R. A.; Paschoarelli, L. C. [UNESP]; Frazão, R. (Crc Press-taylor & Francis Group, 2013)
Packaging for frozen foods is characterized by technological and commercial development, but also leads to negative environmental impact. The present study assessed mock-ups developed by a packaging design method based on principles for sustainability («sustainable») and by a conventional design method («control»). A group of experts analysed eight mock-ups following two criteria: minimization of resources and the application of recycled and renewable materials. The results show that the mock-ups resulting from the «sustainable» process were significantly (p ≤ 0.05) better assessed. This represents a step forward in methodological studies regarding packaging design that contributes to sustainable development. © 2013 Taylor & Francis Group.